Disseminação de informações geográficas nos municípios do estado de Goiás: contexto, obstáculos e perspectivas frente ao auxílio à tomada de decisões - Silva, Wanessa Campos (2017)
This research analyzes issues related to the use of geographic information and GIS in municipal public management, especially in relation to environmental issues. It presents a profile of certain municipalities in the State of Goiás, based on an unpublished survey through a structured questionnaire, geared to the use, production and dissemination of information and geographic data, encompassing all municipalities in Goiás in the year 2016. The analysis was complemented with socioeconomic, environmental and planning information provided by the IBGE's Basic Information Survey, and the LAPIG Territorial Intelligence tool, present in its Portal / Interactive Map, in order to raise the use of geographic information and GIS in its management processes, with reference also to some aspects of environmental conservation. Of the 246 municipalities surveyed in Goiás, only 15 had some type of geographic information available on the internet. Looking for the contact of each municipality for the application of the questionnaire, only 171 had valid contact that made the research feasible. Of these 171, only 18 answered the questionnaire, defining the sample universe of the research. Based on a general analysis of these three sources of information, it is known that most of the municipalities analyzed make frequent use of GIS tools, including the production of data and geographic information, as well as specific mappings. However, heavily structured municipalities with regard to computerization and cartography of their processes still don’t provide information and data in an effective and accessible way (such as Goiânia, for example), showing deficiencies and potential in the scope of municipal public management in Goiás. The participation of state and federal public institutions within the Metropolitan Region of Goiânia (RMG) are vital means and partnerships for better dissemination of territorial management of municipalities, as well as for the encouragement and consolidation of a cartographic culture throughout the management and municipal planning.